Health literacy levels and its determinants among people with asthma in Malaysian primary healthcare settings: a cross-sectional study - H. Salim; S. Shariff Ghazali; P. Y. Lee; A. T. Cheong; N. H. Harrun; S. Mohamed Isa; H. Pinnock (BMC, 2021)
Abstract Background Limited health literacy among people with asthma is associated with poor adherence to self-management activities, thus poor clinical outcomes. This study aimed to determine the prevalence of health literacy level and its determinants among people with asthma in the Malaysian primary healthcare settings. Method A cross-sectional study was conducted among participants aged > 18 years with asthma who attended five primary health clinics in Malaysia. Systematic random sampling was employed with a final sample of 550 participants. The questionnaires included the validated Malay version of Health Literacy Scale (HLS) and asthma control questionnaire (ACQ). Statistical analysis was done using SPSS version 25. Multiple logistic regression was performed to determine the determinants for limited health literacy. Results The participants mean age of the participants was 48 (SD15.4) years. Most of the participants were women (64%) and of Malay ethnicity (51.1%). Nearly half had a secondary level of education, n = 112, (45.8%). Mean duration of asthma diagnosis is 20.6 (SD 15.9) years. More than half (62.5%) had a family history of asthma. About half (50.9%) had uncontrolled asthma, with 87.3% self-rated themselves as having controlled asthma. About a third (29.1%) received education on of asthma action plan, but only 7.1% of these owned a written version an asthma action plan. Limited health literacy accounts for 60.5% of the participants. The significant determinants for limited health literacy included lower educational attainment (p < 0.001), family history of asthma (p = 0.034), < 20 years duration of asthma diagnosis (p = 0.031) and not receiving asthma action plan education (p < 0.001). Conclusion In this study population, more than half of the people living with asthma were found to have limited health literacy, which was associated with not having received self-management education supported by an asthma action plan. Future interventions should include strategies that ensure they meet the needs of people with limited health literacy.